Ways for the Prosperity of Farmers in Western Hills and Terai, Nepal - Amgain, L. P.; Dawadi, A.; Adhikari, A.; Timilsina, K. (Journal of Tikapur Multiple Campus, 2023)
The Institute of Agriculture and Animal Science (IAAS) under Tribhuvan University (TU) has launched the internship programme me for their final semester students studying under-graduate level since 2014/15 in its all constituent and affiliated campuses. About 106 UPA mini-theses accomplished by 221 B.Sc. Ag. graduates from the Prithu Technical College (PTC) libraries were systematically arranged and categorized in chronological order based on the disciplinary subjects and thematic areas, and the technologies have been recommended to scale-out for the prosperity of the farmers in the western Tertian mid-hill agro-ecology of Lumbini and adjoining provinces in Nepal. The review revealed that the researches at PTC were concentrated majorly on major food grain crops with five major themes viz. varietal evaluation, crop management, soil nutrient, weed and insect pest management. The review further revealed that the adequate number of researches were in the vegetable crops specially in production packages and value-chain analysis followed by the control of insect pests and diseases both in on-farm and storage structures, suggesting to follow the integrated pest management (IPM) approach. Varietal testing in major field and vegetable crops, and economic survey of chamomile, marigold, honeybees, broiler chicken, cardamom and ginger and oyster mushroom cultivation practices are the newly defined arena to be adopted for harnessing the prosperity of the farmers of the western hills and Terai region in Nepal and its adjoining congenial agro-climatic environment. Future collaboration with the various agriculture related national and international organizations as adopted by PTC on these recent years has to be continued and strengthened further to extrapolate the UPA research innovations obtained from the graduate student’s mini-thesis works.